Hyperbaric oxygen therapy: The efficacy in the treatment of diabetic foot injury - Cunha, Camila Pereira Lobato Da; Araújo, Thaís Santos De; Adorno, Wanessa Carolinna Linhares Diniz (Revista Feridas, 2019)
Hyperbaric Oxygen Therapy (HBOT) is a therapeutic adjuvant in which the patient receives 100% pure pressurized oxygen, widely used in chronic injuries, such as injury and amputation in diabetic foot - one of the most frequent complications of Diabetes Mellitus (DM). This integrative literature review aims to identify data from studies that prove the efficacy of HBOT as a complementary therapy in the treatment of diabetic foot injury. Articles were searched in the Scielo database, Bireme and the PubMed and fifteen were selected to compose the sample. Through the analysis of the articles, significant reductions in amputation rates were evidenced, in addition to the high rate of partial tissue reconstitution and total healing of chronic wound in diabetic foot. Statistical data show HBOT as an adjuvant and effective therapy in the treatment of diabetic foot lesion, through comparative studies and research in which several authors found improvement of these lesions, reaffirming its effectiveness.